Length-Weight Relationship of Bullet Tuna (Auxis rochei) Landed at Kendari Ocean Fishing Port - Muh. Aksa Azis; Raut Wahyuning Paluphi; Raut Nugrahening Widhi; Disnawati Disnawati (Jurnal Biologi Tropis, 2026)
Bullet tuna (A. rochei) is a species of pelagic fish that holds significant economic importance and serves as a source of livelihood for fisherman. The purpose of this study was to determine length-weight relationship of bullet tuna (A. rochei) landed at Kendari Ocean Fishing Port. Sampling of bullet tuna (A. rochei) using random sampling method. The analysis used in this study is linear regression analysis. The results of the study indicate that 600 rochei tuna (A. rochei) caught ranged in length from 152 to 265 mm and weighed between 70 and 285 grams. The length and weight of bluefin tuna (A. rochei) were strongly correlated (r = 0.68) with a negative allometric growth pattern (b = 2.0175). These results suggest that the rate of length growth is more dominant than the rate of weight gain in fish. The growth patterns obtained from the results of the length-weight relationship research are crucial for sustainable fisheries management, such as regulating the selectivity of fishing gear.